2015
DOI: 10.1136/vr.102580
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the aerobic bacterial flora of boid snakes: application of MALDI‐TOF mass spectrometry

Abstract: The aim of this study was to identify aerobic bacterial isolates from the respiratory tract of boids with matrix-assisted laser desorption ionisation-time-of-flight mass spectrometry (MALDI-TOF MS). From 47 boid snakes, swabs from the oral cavity, tracheal wash samples and, in cases in which postmortem examination was performed, pulmonary tissue samples were taken. Each snake was classified as having inflammation of the respiratory tract and/or oral cavity, or without evidence of inflammation based on combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…In doing so, we have shown that this method provides a wealth of biological information for novel species discovery through microbial community profiling, and have described the presence of highly abundant bacterial species at these sites, some of which have not previously been described. The animal and public health implications of these findings are unknown, but the repeated observations of human pathogens in the microflora of snakes 21 , 22 and other reptiles warrants further investigation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In doing so, we have shown that this method provides a wealth of biological information for novel species discovery through microbial community profiling, and have described the presence of highly abundant bacterial species at these sites, some of which have not previously been described. The animal and public health implications of these findings are unknown, but the repeated observations of human pathogens in the microflora of snakes 21 , 22 and other reptiles warrants further investigation.…”
Section: Resultsmentioning
confidence: 98%
“…and Luteimonas sp . in the respiratory tract 21 , 22 and Serratia marcescens , Pseudomonas aeruginosa and Salmonella enterica in the cloaca 23 . Interestingly, Chitinophageaceae appeared to dominate the choana samples, which has not been described before.…”
Section: Resultsmentioning
confidence: 99%
“…Diskutiert wird in der Literatur auch eine fehlerhafte Einordnung der Bakterien bei Identifizierung durch die früher häufig genutzte "Bunte Reihe" bzw. den Analytical Profile Index (API) anstatt des MALDI-TOF-MS-Verfahrens [29]. Dies ist im Einzelfall durchaus möglich, doch werden auch in früheren Arbeiten viele der in dieser Studie nachgewiesenen Bakterienspezies beschrieben.…”
Section: Diskussionunclassified
“…Despite the advantages of MALDI-TOF MS for routine identification of bacterial isolates, several papers have revealed problems with the identification of various isolates using MAL-DI-TOF MS [18,23]. Identification has been found to be unreliable at the species level for several genera [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…These problems are usually known to the manufacturer, and a comment appears if one of these species is considered as a probable result by MALDI-TOF MS, even if an appropriate score is achieved. Nevertheless, results considered unreliable (score < 1.70) occur frequently in veterinary diagnostics [18] and bacteria isolated from minor species such as reptiles seem especially frequently affected [23]. In the worst case this could lead to treatment errors affecting the health of the patient.…”
Section: Introductionmentioning
confidence: 99%